Installation of Religious Moderation Values in Multi Ethnic And Religious Communities in Polagan Galis Pamekasan Village - Fithriyah, Imaniyatul (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2023)
This research aims to reveal and provide an interpretation of the results of research on the inculcation of the value of religious moderation by the Miftahul Qulub Islamic boarding school in multi-ethnic and religious communities. This research method uses a qualitative approach because the data produced is in the form of words, while the type of research is a case study because it wants to reveal the process of instilling the value of religious moderation by Islamic boarding schools in the formation of an inclusive, friendly community that is able to live side by side with ethnic and religious differences. Data were obtained through observation, interviews, and the study of documents related to the research theme. The research data were then analyzed through an interactive analysis model, namely through data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that the process of cultivating religious moderation values carried out by Islamic boarding schools in their efforts to form a multi-ethnic and religious society that is harmonious, friendly, tolerant, and coexisting in differences in both ethnicity and religious belief is through a habituation process, an integration process, a reflective process, and the process of transinternalization and social assimilation based on social community and socio-religious in the village of Polagan Galis Pemakasan.